Unhealthy lifestyle factors among wellness student at umk city campus - Balqis Nur Athira Mohd Zulmizan; Rabiatuladawiyah Zawadod; Nurul Kiasatina Kaparom @ Harun; Fatin Nadirah Lan (2023)
The Health Sector in Malaysia lacks emphasis on awareness of the consequences of unhealthy food in the community. This is because Malaysia is considered a country with unhealthy people. The purpose of this study is to see the factors that influence the unhealthy lifestyle of Wellness students at City Campus. The aim of this study is to discover the factors that influence the unhealthy lifestyle of Wellness students at City Campus such as hereditary diseases, and psychological and peer influence. These factors are important in building awareness of unhealthy lifestyles in Wellness students. The main data of this study will be collected using a structured questionnaire method and data analysis will be done using SPSS software. This survey will be distributed to 242 respondents from UMK City Campus Wellness students. The Malaysian health industry has organized various campaigns to promote good health. Therefore, through this study the researcher tried to find out and study the factors that influence the unhealthy lifestyle of Wellness students.